IMPORTANT ROLE OF SUPERVISION AND ITS IMPACT ON PERFORMANCE OF MANPOWER AND TRANSMIGRATION DEPARTMENT OF EAST OKU - Margahana, Helisia (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
Resources owned by agencies will not provide optimum results if they are not supported by human resources who have optimum performance. Assessing the quality of existing human resources can be measured by employee performance. Performance can be a means for an agency to measure the ability of employees in an agency. This study aims to determine and analyze the important role of supervision and its impact on employee performance of Manpower and Transmigration Office at the East OKU. The hypothesis proposed is the existence of a strong influence between supervision on employee performance of Manpower and Transmigration Office at the East OKU.From the calculation results obtained r = 0.368. After consultation with conservative standards it turns out that 0.368 is located between 0.200 - 0.399 which is included in the low correlation. Then to answer the hypothesis test proposed in the previous chapter has a relationship or not, then tested with a hypothesis test and obtained t count = 1.118. While the t table value at the 95% confidence level for (n - 2) = 1,860. Then it can be seen that the t value of 1.118 is greater than the value of t table that is = 1.860, thus it means that (Ho) can be accepted and (Ha) rejected